Long term effects of gamma radiation on inflammatory and apoptotic biomarkers in nuclear medicine staff - Niha, Mahdiyeh Mirnam; Barough, Mehdi Salehi; Saniei, Elham; Banaee, Nooshin (Journal of medical imaging and radiation sciences, 2025)
Gamma radiation at low doses might have potential health effects in long-term exposure. The current study was aimed to search cell death pathway and inflammatory biomarkers in nuclear medicine workers with long-term exposure to gamma radiation. Fifty cases with a history of 10 years' exposure to gamma radiation and 30 normal individuals were included in the current study. Blood samples were collected and then analyzed for gene expression of apoptotic markers, pro-inflammatory factor TNF-a, and antioxidant enzymes using Real Time PCR (RT-PCR) in both groups. Protein expressions were examined by Western blot and trace elements were analyzed using atomic absorption spectrometry. In exposed group, the expression of pro-apoptotic markers (CASP 8, CASP 3, Casp 9, and BAX genes), the pro-inflammatory factor TNF and antioxidant enzymes such as SOD, CAT, and GPX was increased in comparison with control group (P < 0.05). However, Bcl2 expression was decreased in exposed group. In addition, there was a significant and inverse correlation between serum levels of zinc and selenium in the exposed subjects compared to the control group (P < 0.05). Our results revealed the potential role of low and chronic doses of gamma radiation in triggering apoptosis and inflammatory responses. However, more studies are needed to consolidate our findings.